POTENSI EKSTRAK KULIT BATANG BUNI (Antidesma bunius L. Spreng) UNTUK MENURUNKAN KADAR GLUKOSA DARAH TIKUS WISTAR HIPERGLIKEMIA - S. R. Santi; I. M. Sukadana; N. W. I. Paramitha (Jurnal Kimia (Journal of Chemistry), 2020)
Buni (Antidesma bunius L. Spreng) is one of the traditional medicinal plants whose stem bark has been proven in vitro as an antidiabetic by inhibiting the activity of the ? glucosidase enzyme. This study aims to determine the potential of ethanol extract of buni bark to reduce blood glucose levels in wistar rats in vivo induced by alloxan. Two groups of control rats K (+) and K (-), and three groups of treated rats (P1, P2, and P3) which were given the extract with a dose of 50, 100, and 200 mg/ kg BW respectively, were induced with 150 mg / kg BW alloxan monohydrate to make the rats hyperglycemic. On the 14th day of the trial (posttest) the average blood glucose level was tested using ANOVA with a = 0.05 and Tamhane's. It was concluded that the 200 mg / kg BW ethanol extract of buni bark was able to reduce blood glucose levels to closer to the normal condition when compared to negative control K(-). Keywords: antidiabetic, Antidesma bunius L. Spreng., GC-MS, stem barks